Effects of Cholinergic Stimulation with Pyridostigmine Bromide on Chronic Chagasic Cardiomyopathic Mice - Marília Beatriz de Cuba; Marcus Paulo Ribeiro Machado; Thais Soares Farnesi; Angelica Cristina Alves; Livia Alves Martins; Lucas Felipe de Oliveira; Caroline Santos Capitelli; Camila Ferreira Leite; Marcos Vinícius Silva; Juliana Reis Machado; Henrique Borges Kappel; Helioswilton Sales de Campos; et al. (Hindawi Limited, 2014)
The aim of the present study was to assess the effects of an anticholinesterase agent, pyridostigmine bromide (Pyrido), on experimental chronic Chagas heart disease in mice. To this end, male C57BL/6J mice noninfected (control:Con) or chronically infected (5 months) with Trypanosoma cruzi (chagasic:Chg) were treated or not (NT) with Pyrido for one month. At the end of this period, electrocardiogram (ECG); cardiac autonomic function; heart histopathology; serum cytokines; and the presence of blood and tissue parasites by means of immunohistochemistry and PCR were assessed. In NT-Chg mice, significant changes in the electrocardiographic, autonomic, and cardiac histopathological profiles were observed confirming a chronic inflammatory response. Treatment with Pyrido in Chagasic mice caused a significant reduction of myocardial inflammatory infiltration, fibrosis, and hypertrophy, which was accompanied by a decrease in serum levels of IFNγ with no change in IL-10 levels, suggesting a shift of immune response toward an anti-inflammatory profile. Lower nondifferent numbers of parasite DNA copies were observed in both treated and nontreated chagasic mice. In conclusion, our findings confirm the marked neuroimmunomodulatory role played by the parasympathetic autonomic nervous system in the evolution of the inflammatory-immune response to T. cruzi during experimental chronic Chagas heart disease in mice.